Human Rights Are The Highest Values - Adkham Jorayev (Global Scientific Publishing, 2024)
Values is a concept with a deep meaning and has attracted the attention of philosophers, cultural scientists, folklorists, ethnographers and others. There are scientific-theoretical, spiritual-ethical, national-historical, philosophical-legal approaches to values in research, scientific-research works, and debates among those interested in this topic. This indicates that values are a comprehensive social phenomenon related to the essence of all spheres of social life important for man and society. A hard-working person who embodies material-spiritual, socio-political, national and universal human values in his language, strives to make life beautiful and prosperous, peace, democracy and a human who wants to start a new life means the highest wealth. The fact that person is a high value is manifested, first of all, in his moral relations to himself and society. Person who has the highest value of life, first of all can make a good relationship with other people.
Keywords: relations; manifested; material; phenomenon